People, governance and forests -- the stumbling blocks in forest governance reform in Latin America - Contreras Hermosilla, A. (MDPI, 2011)
This article examines common barriers to achieving adequate levels of forest resource governance in countries of Latin America. It looks at the deficiencies of the policy and regulatory frameworks affecting forests, the common failure to impose the rule of law, the main factors that constrain the effectiveness of government actions in the forest sector and at the political barriers to introducing reforms for change in governance structures. The elimination of these barriers acquires new importance in the implementation of successful REDD+ programs in the countries of the region.